2005
DOI: 10.1089/ten.2005.11.974
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F127 as a Cell Encapsulation Material: Utilization of Membrane-Stabilizing Agents

Abstract: Thermoreversible gelation of the copolymer Pluronic F127 (generic name, poloxamer 407) in water makes it a unique candidate for cell encapsulation applications, either alone or to promote cell seeding and attachment in tissue scaffolds. At concentrations of 15-20% (w/w), aqueous Pluronic F127 (F127) solutions gel at physiological temperatures. The effect of F127 on viability and proliferation of human liver carcinoma cells (HepG2) was determined for both liquid and gel formulations. Cell concentration and viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
188
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(201 citation statements)
references
References 37 publications
11
188
2
Order By: Relevance
“…Previous studies have shown cytotoxic effects when F127 is used as an encapsulating gel (60%-70% viability for 15.6 wt% F127), but not when used as a liquid additive (80%-90% viability for 10 wt% F127), with more severe effects at higher weight percentage and longer exposure time (quoted fi gures for HepG2 cells, t = 1 d). [ 32 ] These values correlate well with the results from our study, where hMSCs are only exposed to 13 wt% F127 during mixing and printing (typically 30-60 min), before F127 is expelled from the hybrid gel. In general, hMSCs encapsulated within the hybrid gel adopted a spherical cell morphology, an equilibrium geometry assumed in the absence of microscale features or integrin binding sites, and typical of nanofi brous gels, such as alginate.…”
Section: Doi: 101002/adhm201600022supporting
confidence: 89%
“…Previous studies have shown cytotoxic effects when F127 is used as an encapsulating gel (60%-70% viability for 15.6 wt% F127), but not when used as a liquid additive (80%-90% viability for 10 wt% F127), with more severe effects at higher weight percentage and longer exposure time (quoted fi gures for HepG2 cells, t = 1 d). [ 32 ] These values correlate well with the results from our study, where hMSCs are only exposed to 13 wt% F127 during mixing and printing (typically 30-60 min), before F127 is expelled from the hybrid gel. In general, hMSCs encapsulated within the hybrid gel adopted a spherical cell morphology, an equilibrium geometry assumed in the absence of microscale features or integrin binding sites, and typical of nanofi brous gels, such as alginate.…”
Section: Doi: 101002/adhm201600022supporting
confidence: 89%
“…It has been shown that cells proliferate and maintain high viability at this concentration of Pluronic ® F127. 27 The alginate solution was injected at a controlled flow rate by a syringe pump ͑Ph.D 22/2000, Harvard Apparatus, USA͒. The pressure was measured by a digital pressure indicator ͑PM, Heise, USA͒.…”
Section: A Microfluidic Devicementioning
confidence: 99%
“…This commercially available family of polymers, some of which are approved for medical use by the FDA, has been tested in many biomedical studies. The most commonly tested Pluronics include Pluronic F68, which has been shown to be a very potent suppressor of carcinogenesis in the colon of rats and mice, 8 Pluronic F127, which demonstrated the ability to penetrate cellular membranes and to stabilize them after being subjected to an external stress, 9 and Pluronic P85, which has been shown to significantly enhance drug permeability through epithelial cells. 10 Due to the many beneficial biological and biomedical properties of Pluronics that have been reported to date, we decided to characterize the interactions forces between Pluronics and lipid membranes using a surface forces apparatus (SFA) to provide a molecular level understanding of the interaction forces that may be at the origin of these reported properties.…”
Section: ■ Introductionmentioning
confidence: 99%